The relationship between the Test of English as a Foreign Language (TOEFL), the International English Language Testing System (IELTS) scores and academic success of international master's students - Arcuino, Cathy Lee T., author; Kuk, Linda, advisor; Gloeckner, Gene W., committee member; Davies, Timothy, committee member; Aoki, Eric, committee member (Colorado State University. Libraries, 2013)
The purpose of this study was to examine if the Test of English as a Foreign Language (TOEFL) and the International English Language Testing System (IELTS) are related to academic success defined by final cumulative grade point average (GPA). The data sample, from three Midwestern universities, was comprised of international graduate students who graduated within 2006-2011. The total number of students records utilized were 793 (35.7% were female and 65.3% were male). The study did not find a significant difference between TOEFL (paper-based, computer-based, and internet-based) and IELTS scores in relation to academic success. Students tended to score higher on TOEFL iBT followed by TOEFL PBT. Indian and Taiwanese students performed better on TOEFL iBT and Chinese and Indian students performed better on the TOEFL PBT. A statistical significance was found among final cumulative GPA and college program of study in relation to TOEFL and IELTS scores. Knowing more about the reasons behind international graduate students' academic success is a benefit to institutions. The findings of this study may help graduate offices in comprehensive Midwestern institutions, with the recruitment and retention of international students. The research may also assist in the evaluation of admission requirements.
Keywords: academic success; TOEFL; international students; IELTS